Umur, Paritas Dan Riwayat Obstetri Dengan Kejadian Perdarahan Post Partum - Ika Putri Damayanti; Rita Afni (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Post partum hemorrhage is bleeding that occurs more than 500 cc in 24 hours after the birth to go. Post partum hemorrhage is divided in two primary post partum hemorrhage and secondary. Post partum hemorrhage occorured more than 500 cc in the first 24 hours are ussualy between 5 to 15 days post partum. Post partum hemorrhage can lead to maternal death if not done the prevention of risk factors.Objective: This study aims to determine the relations of the factors that influence the occurence of post partum hemorrhage at Arifin Achmad in Riau province in 2012.Methode: The research uses a quantitative analytical case control design. Number of 180 subject consisted of 90 180 cases and 90 controls. Measuring instrument used are no check-list table. Unvariate and bivariate data analysis with chi-square test.Result: The result showed that maternal age <20 years and >35 years 2,9 times more at risk than maternal age 20-35 years, with OR=2,991 (95% CI 1,630 to 5,489), parity >4 children 2 times more at risk than parity < 3 children with value OR=2,091 (95% CI 1,145 to 3,819), and obstetrics history with action 2 times more at risk than spontaneous labor with a value of OR=2,275 (95% CI 1,247 to 4,148).Conclusion: The conclusion from this study is that there is a relationship between age, parity and obstetric history with post partum bleeding events.Keyword: Age, Parity and History with Genesis Obstetrics